The Influence of Product Quality and Price Perception on Purchase Decisions for Gold Savings Products - PRATIWI, Ni Komang Rada; PUTRA, Komang Endrawan Sumadi (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to determine the effect of product quality and price perception on consumer purchasing decisions on gold savings products. This type of research is quantitative research. The population used is customers who buy gold at PT. Pegadaian UPC Lovina, Buleleng Regency in 2024. The sampling technique used is probability sampling with the simple random sampling method. Determination of the number of samples using the Slovin formula, so that the number of samples used is 400 respondents. The instrument used in data collection is a questionnaire. Data processing in this study uses the assistance of the Statistical Package for The Social Science (SPSS) version 25 program. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that: (1) Product quality and price perception have a positive and significant effect on customer purchasing decisions on gold savings products, (2) Product quality has a positive and significant effect on customer purchasing decisions on gold savings products and (3) Price perception has a positive and significant effect on customer purchasing decisions on gold savings products.